Spectral studies of silver nanoparticles biosynthesized by Origanum majorana - Zahran, Moustafa; El-Kemary, Maged; Khalifa, Shaden; El-Seedi, Hesham (De Gruyter, 2018)
Silver nanoparticles (AgNPs) were biologically synthesized in an eco-friendly manner using aqueous leaf extract of Origanum majorana plant and silver nitrate (AgNO3) solution. Size, shape, and crystallinity of the biosynthesized AgNPs were determined by using a transmission electron microscope (TEM). Zeta potential analyzer was used to prove the stability of the metallic nanoparticles, while Fourier transform infrared spectroscopy was used to identify the bioreducing and capping agents. AgNPs were electrochemically investigated using cyclic voltammetry (CV), while the optical properties of the metallic nanoparticles were studied using UV-Vis and fluorescence spectroscopies. According to TEM images, AgNPs are spherical with an average size of 35 nm. TEM also refers to the presence of mono and polycrystalline AgNPs. The value of zeta potential (-39 mV) proved the stability of AgNPs caused by capping molecules of O. majorana plant. CV studies showed that AgNPs were electrochemically investigated at 0.39 mV. AgNPs showed a surface plasmon resonance peak at 440 nm, while the emission peak was detected at 466 nm. These nanoparticles are promising for many industrial and medical applications.